FACTORS AFFECTING FORMATION OF FINANCIAL STABILITY IN INDUSTRIAL ENTERPRISES (Marketing Journal, 2025)
This article provides a scientific and practical analysis of internal and external factors shaping the financial sustainability of industrial enterprises, particularly those operating in the oil and gas sector. The study examines the interrelationships amo ng factors affecting financial sustainability, the mechanisms of their direct and indirect influence, and the specific features of their manifestation under conditions of economic instability. The possibilities of mitigating the negative impact of the exte rnal environment through effective management of internal factors are substantiated.
Keywords: financial sustainability; industrial enterprises; internal and external factors; economic instability; financial indicators; management system; asset turnover; risks; strategic management. № 1 509